Shaping the Political Image: Kamala Harris’s Case - Vilma Linkevičiūtė (Journalism and Media, 2025)
This research aims at identifying the prevalent conceptual metaphors in Kamala Harris’s discourse and analysing their role, function and significance in shaping her personal image and the image of her political opponent Donald Trump. This research was conducted using a qualitative research method and applying a conceptual framework, encompassing political discourse analysis and Conceptual Metaphor Theory. Harris’s pre-election political discourse demonstrates a three-dimensional image formation model, including conceptual models as the main image shaping tool: conceptual metaphors aimed at Harris and the political party she represents; conceptual metaphors targeted at her political opponent Donald Trump; and bi-directional conceptual metaphors aimed at both competitors, but targeted at forming reverse images and evoking opposite connotations, with diverse goals. Conceptual metaphors, aimed at a positive formation of Harris’s image, include the following: STATE IS A BUILDING, STATE IS A PERSON and POLITICS IS A PLANT. A negative image of Trump is shaped upon the following conceptual metaphors: POLITICS IS WAR, POLITICS IS CHAOS, POLITICS IS BUSINESS, POLITICS IS A RACE, POLITICS IS FICTION, POLITICS IS A BURDEN, and POLITICS IS A RELATIONSHIP. The bi-directional group comprises such conceptual metaphors as POLITICS IS A KNIFE, POLITICS IS A CRIME, POLITICS IS LOVE, POLITICS IS A JOURNEY and POLITICS IS A BOOK.